On the perception of the radio play - Blaustein, Leopold (Phainomena (Ljubljana), 2025)
Blaustein explores the phenomenon of listening to the radio play. The idea put forth by the author is that the radio play engages perception, treating the latter in a broad sense. Perception is not necessarily restricted to seeing; rather, it is understood as being cross-modal, as involving different senses. The main sense involved in the case of radio plays is hearing, which enables one to listen to the radio. Radio listeners are drawn into radio plays as media of hearing. Instead of vision, listeners engage their “acousion,” a term coined by Blaustein to capture the perceptual distinctness of hearing; acousion is the auditive perception of radio plays. Listening to a radio play is a lived experience or a psychic phenomenon, precisely due to the activeness of acousion. Listeners do not only passively perceive or hear auditive data. They also engage their imaginative faculties, presenting to themselves, mentally, the world of the action; by so doing, listeners enable the act of listening. According to Blaustein, presentations, even imaginative ones, are basic. By listening to a radio play, the listener imaginatively presents the world of the action to themselves, as if they were watching a theater play. However, going beyond the realm of presentations, other factors are examined, e.g., the listener’s focus is turned into the world represented—the world within—, which is given to them via auditive data and dialogue.
Keywords: aesthetic experience; domišljija; estetsko izkustvo; hearing; imagination; listening; perception; poslušanje; radijska igra; radio play; sluh; zaznavanje